Studies On Immunomodulatory Activity Of Flavonoid Fractions Of Terminalia Catappa In Swiss Albino Mice - M.SAROJA; R.SANTHI; S.ANNAPOORANI (International Journal of Pharma and Bio Sciences, 2012)
To investigate the immunomodulatory activity of flavonoid fractions of Terminalia catappa in Swiss albino mice. The flavonoid fraction of T.catappa was administrated intraperitonealy at a dose of ED50 to healthy albino mice. Assessment of immunomodulatory activity was carried out by assessment of neutrophil adhesion and phagocytic index. Intraperitonealy administered Tcff showed a significant increase in neutrophil adhesion and phagocytic index.This study demonstrates that the Tcff shows immunomodulatory effect.